2013
DOI: 10.1007/978-3-642-36700-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Tangible Images: Bridging the Real and Virtual Worlds

Abstract: In this paper we describe our efforts to create tangible imaging systems that provide rich virtual representations of real-world surfaces. Tangible imaging systems have three main properties: 1) the images produced must be visually realistic; 2) the images must be responsive to user interaction; and 3) the images must be situated, appearing to be integrated with their environments. Our current system, based on a computer, LCD display, light and position sensors, and graphics rendering tools meets all these req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The final observation is from the Ferwerda and Darling proposed framework, which aims to develop imaging technology that bridges the real and virtual worlds 41 . The authors identified three requirements: (a) the images produced by the systems must be realistic, accurately representing the shapes and material properties of the modelled surfaces; (b) the images must be responsive, changing appearance appropriately with direct manipulation and changes in the observer viewpoint; and (c) the images must be situated, appearing to be an integral part of the observer's environment.…”
Section: D Model Colour Acquisition Management and Visualisation Prmentioning
confidence: 99%
“…The final observation is from the Ferwerda and Darling proposed framework, which aims to develop imaging technology that bridges the real and virtual worlds 41 . The authors identified three requirements: (a) the images produced by the systems must be realistic, accurately representing the shapes and material properties of the modelled surfaces; (b) the images must be responsive, changing appearance appropriately with direct manipulation and changes in the observer viewpoint; and (c) the images must be situated, appearing to be an integral part of the observer's environment.…”
Section: D Model Colour Acquisition Management and Visualisation Prmentioning
confidence: 99%